Investigating voluntary workplace green behaviours in Brazil - Renwick, D. W.S.; Brint, Andrew; de Camargo Fiorini, Paula [UNESP]; de Sousa Jabbour, Ana Beatriz Lopes; Jabbour, Charbel José Chiappetta (Springer Nature, 2024)
We develop and test an original framework to explain what influence group workplace green cultural environment has on Voluntary Workplace Green Behaviour (VWGB), and how changing a group's green culture likely impacts VWGB. Using data collected from four firms located in Brazil, a multilevel model is employed with VWGB being split into between and within group components. Study findings reveal that VWGB within groups is substantially affected by how high each group member rates their individual moral outlook and they assess the group's green culture, and between groups average views of a group's green culture significantly correlate correlation with group average VWGB. Unexpectedly, no strong linkage emerged between the group leader's self-assessed VWGB and the group member's assessment of its green culture. Our findings pose implications for the possibilities and challenges of transforming firm sustainability in emerging economies.
Keywords: Behaviour; Brazil; Culture; Green; Sustainability; Teams; Voluntary; Workplace